LIRIS (Literasi dan Riset) sebagai Inovasi pada Problematika Gerakan Literasi Sekolah dalam Pembelajaran Sejarah di SMAN 1 Sumenep - Supriyono, Agus; Hariyono, Hariyono; Wahyudi, Deny Yudo (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
Literacy activities in education hold a crucial position, particularly reading within history education. Addressing literacy challenges encountered in the history learning process at State Senior High School (SMAN) 1 Sumenep, there arises a necessity for innovation in implementing school literacy movements. LIRIS stands as an innovative initiative formed by the School Literacy Team (Tim Literasi Sekolah/TLS) at SMAN 1 Sumenep, aimed at addressing literacy challenges by amalgamating literacy processes with research. This research aims to find out the implementation and problems of history learning in the GLS program and find out how LIRIS can be an innovation in literacy activities. Employing a qualitative descriptive approach, data is collected through interviews, observations, and documentation, then analyzed through data reduction, presentation, and verification. Findings reveal: (1) GLS implementation in history education generally follows existing guidelines, observable in familiarization, development, and learning stages, yet specifics vary based on classroom conditions and teacher innovation, (2) literacy activity issues in history education arise across student, teacher, and school support aspects, and (3) LIRIS emerges as an innovative literacy activity addressing both general and specific history education challenges, albeit still necessitating evaluation and refinement.